Genome-wide association study of loss of heterozygosity and metastasis-free survival in breast cancer patients - Deryusheva, I.V.; Tsyganov, M.M.; Garbukov, E.Y.; Ibragimova, M.K.; Kzhyshkovska, Ju.G.; Slonimskaya, E.M.; Cherdyntseva, N.V.; Litviakov, N.V. (Experimental Oncology, 2017)
One of the factors providing the diversity and heterogeneity of malignant tumors, particularly breast cancer, are genetic variations, due to gene polymorphism, and, especially, the phenomenon of loss of heterozygosity (LOH). It has been shown that LOH in some genes could be a good prognostic marker. Aim: To perform genome-wide study on LOH in association with metastasisfree survival in breast cancer. Materials and Methods: The study involved 68 patients with breast cancer. LOH status was detected by microarray analysis, using a high density DNA-chip CytoScanTM HD Array (Affymetrix, USA). The Chromosome Analysis Suite 3.1 (Affymetrix, USA) software was used for result processing. Results: 13,815 genes were examined, in order to detect LOH. The frequency of LOH varied from 0% to 63%. The association analysis identified four genes: EDA2R, PGK1, TAF9B and CYSLTR1 that demonstrated the presence of LOH associated with metastasis-free survival (log-rank test, p < 0.03). Conclusions: The presence of LOH in EDA2R, TAF9B, and CYSLTR1 genes is associated with metastasis-free survival in breast cancer patients, indicating their potential value as prognostic markers.